Interleukin-15 and innate effector cells as predictors of outcome in allogeneic hematopoietic cell transplantation - Warny, Marie; Ostrowski, Sisse Rye; Petersen, Søren Lykke; Friis, Lone Smidstrup; Kornblit, Brian Thomas; Andersen, Niels Smedegaard; Schjødt, Ida; Larsen, Margit Hørup; Møller, Janne Amstrup; Haastrup, Eva Kannik; Sengeløv, Henrik; Minculescu, Lia (Frontiers in Immunology, 2026)
IntroductionImmune reconstitution is a critical parameter in successful hematopoietic cell transplantation (HCT) and involves different cell types and a microenvironment including cytokines. Natural killer (NK) cells and γδ T cells are known to repopulate early after HCT and are proposed to have the intriguing capacity of mediating graft-versus-leukemia (GVL) effects without accompanying graft-versus-host-disease (GVHD). Interleukin-15 (IL-15) and interleukin-7 (IL-7) are key homeostatic cytokines, with effects on both T and NK cells, making these cytokines especially interesting in an HCT setting.MethodsIn this prospective study, we investigated associations between IL-15 and IL-7, NK cells and γδ T cells, including activated subtypes, and clinical outcomes. We included 105 patients undergoing allogeneic HCT at a single-center institution. IL-15, IL-7, and extended T and NK cell phenotyping were measured longitudinally at fixed time points following HCT.ResultsWe found high IL-15 concentrations early post-transplant to be significantly associated with reduced overall survival, reduced relapse-free survival, and excess acute GVHD. Furthermore, IL-15 showed significant inverse correlations with NK cells and γδ T cells, including activated subtypes early after HCT, and with conventional T cells at later time points. IL-7 was significantly inversely correlated not only with conventional T cells but also with γδ T cells early after HCT.DiscussionThese findings may suggest that early immune reconstitution of NK cells and γδ T cells is influenced by the bioavailability of IL-15 after HCT and that IL-15 could have a mechanistic effect in the activity of these innate effector cells. NK cells and γδ T cells are currently being investigated in several promising treatment settings, and IL-15 here may offer a potential benefit.